2011
DOI: 10.1016/j.ssc.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the fractional quantum Hall effect in topological insulators

Abstract: With the recent observation of graphene-like Landau levels at the surface of topological insulators, the possibility of fractional quantum Hall effect, which is a fundamental signature of strong correlations, has become of interest. Some experiments have reported intra-Landau level structure that is suggestive of fractional quantum Hall effect. This paper discusses the feasibility of fractional quantum Hall effect from a theoretical perspective, and argues that while this effect should occur, ideally, in the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In order to see that, let us revise (and specify to our setup) the two main assumptions that are commonly used to study interacting gases within a LL picture: namely, the lowest LL approximation and the formalism of HPs [24]. Such a path has been demonstrated successful in a wealth of physical systems, ranging from usual quantum Hall setups (see, e.g., [25] and references therein) to graphene [26][27][28] and topological insulators [29].…”
Section: Haldane Pseudopotentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to see that, let us revise (and specify to our setup) the two main assumptions that are commonly used to study interacting gases within a LL picture: namely, the lowest LL approximation and the formalism of HPs [24]. Such a path has been demonstrated successful in a wealth of physical systems, ranging from usual quantum Hall setups (see, e.g., [25] and references therein) to graphene [26][27][28] and topological insulators [29].…”
Section: Haldane Pseudopotentialsmentioning
confidence: 99%
“…The LL structure is indeed preserved and simply undergoes a deformation, that splits the degeneracy among internal states and leads to a sequence of different LLs as lowest energy states as a function of the spin-orbit coupling. The effective interaction between atoms in these deformed Landau levels (DLLs) can be described in terms of Haldane pseudopotentials (HPs) [24] (i.e., one coefficient per each relative angular momentum between particles), as proposed in diverse physical systems displaying an effective LL structure [25][26][27][28][29]. In the case of ultracold gases subjected to the considered U (2) gauge potential, it has been shown that even a bare contact interaction between the atoms yields two-particle HPs in the DLLs that dramatically vary with the spin-orbit coupling and introduce effective finite-range interactions [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental observation of topological surface states (SSs) in three-dimensional bulk solids has allowed the study of a correlated chiral Dirac fermion system, which can host a single Dirac valley without spin degeneracy [3][4][5][6][7][8][9][10]. Recent theoretical studies suggest that the fractional quantum Hall effect (FQHE) might be observable in topological insulators [11,12]. However, due to the dominant bulk conduction it is difficult to probe the strong correlation effect in topological insulators from resistivity measurements [8,9].…”
mentioning
confidence: 99%
“…Theoretically, the relativistic nature of Dirac fermions is believed to significantly modify the electron-electron interactions, with the possibility to produce more robust ground states at the n = 1 Landau level (LL) in TIs than in conventional two-dimensional electron systems [20][21][22][23]. The unique spin texture and the coexistence of non-insulating bulk states also raise the intriguing question of whether TIs may host exotic FQH states owing to the non-trivial Berry's phase [16], huge Zeeman energy [24], and the screening effect from bulk carriers [11]. The potential realization of more stable non-Abelian FQH states in TIs is of practical interest for topological quantum computing [12,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation